1968
DOI: 10.1182/blood.v32.1.59.59
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary, X-Linked, Sideroachrestic Anemia. The Isolation of Two Erythrocyte Populations Differing in Xga Blood Type and Porphyrin Content

Abstract: 1. Two morphologically distinct populations of erythrocytes were found in a mother and in two of her daughters, one of whom (the proband) was anemic. One erythrocyte population was morphologically normal; the other was hypochromic and microcytic. 2. The X-linked blood group antigen, Xga, was present in erythrocytes from the mother and the two daughters, but not in erythrocytes from the father. The daughters were, therefore, heterozygous for the gene controlling this antigen. 3. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…It was suggested that the majority of in vitro CFUE may represent the progeny of residual normal erythropoietic stem cells that reside in SA bone marrow along side those stem cells that give rise to SA. In fact, the existence of an abnormal stem cell clone for IASA has been suggested by Bottomley [ 11, and demonstrated in hereditary SA by Lee et a1 [14] and Pasanen et a1 [ 151. Thus, SA may be a clonal disease, and culture of bone marrow cells from these patients in methylcellulose may offer the proper microenvironment for stem cell clones to undergo an otherwise suppressed erythroid differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…It was suggested that the majority of in vitro CFUE may represent the progeny of residual normal erythropoietic stem cells that reside in SA bone marrow along side those stem cells that give rise to SA. In fact, the existence of an abnormal stem cell clone for IASA has been suggested by Bottomley [ 11, and demonstrated in hereditary SA by Lee et a1 [14] and Pasanen et a1 [ 151. Thus, SA may be a clonal disease, and culture of bone marrow cells from these patients in methylcellulose may offer the proper microenvironment for stem cell clones to undergo an otherwise suppressed erythroid differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…With the exception of rare multi-organ syndromes, the inherited forms of sideroblastic anaemia are typically microcytic (Cooley, 1945;Harris & Horrigan, 1964;May & Fitzsimons, 1994). Female carriers may have a dimorphic red cell picture and ring sideroblasts, but are not usually anaemic (Lee et al, 1968;Holmes et al, 1990). However, affected females in several kindreds (presumably X-linked) were anaemic (proband in Weatherall et al, 1970, andLee et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Female carriers may have a dimorphic red cell picture and ring sideroblasts, but are not usually anaemic (Lee et al, 1968;Holmes et al, 1990). However, affected females in several kindreds (presumably X-linked) were anaemic (proband in Weatherall et al, 1970, andLee et al, 1968). Autosomal inheritance of sideroblastic anaemia is rare (Amos et al, 1988;Jardine et al, 1994;van Waveren Hogervorst et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous females may be mildly affected (Garby et al 1957, Losowsky & Hall 1965, Prasad et al 1968). However, one severe (Hilton 1959) and three moderately severe cases (Heilmeyer 1962, Lee et al 1968, Weatherall et al 1970) have been described in females.…”
mentioning
confidence: 99%
“…The occurrence of this usually X-linked disease in females has in one patient been explained on the basis of the Lyon hypothesis of X-chromosome inactivation (Lee et al 1968), but in another (Weatherall et al 1970) this explanation could not be accepted.…”
mentioning
confidence: 99%